International Students’ English Language Learning Experiences: Academic Literacy in Graduate School - Sary Silvhiany (LINGUA: Jurnal Bahasa dan Sastra, 2018)
Abstract: This case study explores the English language experiences and academic cultural adjustment of international doctoral students in the USA. Participants included three doctoral students from three different countries who are at different stages of their study. Using literacy memoir, interview, and email reponses as data collection methods, the study was aimed to un- derstand the factors affecting the students’ academic cultural adjustment. Thematic analysis re- veals that the students’ academic adjustment was influenced by their prior English language ex- periences which provided limited opportunities to develop language skills through meaningful communicative interactions. The different classroom culture and expectations had also affected the students’ academic literacy performance in their academic programs. Implications of the study highlights the need for university as the host institution of these international students to be more sensitive to different cultural capitals and the need for the sending countries to reform their curriculums to accommodate active English communication in the academic contexts.Keywords: cultural adjustment, academic literacy, international studentsAbstrak: Studi kasus ini mengeksplorasi pengalaman belajar bahasa Inggris dan penyesuaian budaya mahasiswa doktoral internasional di Amerika Serikat. Partisipan penelitian ini terdiri dari tiga mahasiswa doktoral yang berasal dari tiga negara dan yang berada pada tahap studi doktoral yang bervariasi. Menggunakan literacy memoir, interview, dan respon melalui surel sebagai metode pengambilan data, studi ini bertujuan untuk memahami faktor – faktor yang mempengaruhi penyesuaian budaya mahasiswa internasional. Analisis tematik menunjukkan bahwa penyesuain budaya mahasiswa internasioanl dipengaruhi oleh pengalaman belajar ba- hasa Inggris di negara mereka yang kurang memberikan kesempatan dalam membangun ket- erampilan melalui interaksi komunikatif yang bermakna. Implikasi penelitian ini menggaris bawahi pentingnya universitas penerima mahasiswa internasional untuk lebih sensitif terhadap perbedaan cultural capital yang dibawa oleh mahasiswa internasional dan perlunya negara pen- girim untuk mereformasi kurikulum mereka agar dapat mengakomodasi pembelajaran bahasa Inggris yang komunikatif dalam konteks akademik.Kata-kata Kunci: penyesuaian budaya, literasi akademik, siswa internasional